Study of Correlation between Used Cooking Oil and Triglyceride Profile on Hypertension in Coastal Communities in Nambo Village, Kendari - Prabowo S. Yuwana; I P. Sudayasa; Tien; Pranita Aritrina (MEDULA: Jurnal Ilmiah Fakultas Kedokteran Universitas Halu Oleo, 2023)
Background: According to the World Health Organization (WHO) in 2008, in Southeast Asia, as many as 36% of adults aged 25 years and over had high blood pressure, and 1.5 million deaths occur each year due to complications of high blood pressure. In Indonesia, hypertension is still a big challenge. This is a health problem with a high prevalence of 25.8% according to Riskesdas data in 2013. Hypertension is a chronic increase in blood pressure 140/90 mmHg. Non-pharmacological therapy needs to be applied to prevent the occurrence of hypertension, namely by modifying lifestyle to control blood pressure. Used cooking oil contains free fatty acids formed from the process of oxidation and hydrolysis, then these free fatty acids reshape saturated fatty acids and trans fatty acids and free radicals, which can cause various disorders such as endothelial dysfunction, which can lead to hypertension. Purpose(s): The purpose of this study was to determine the correlation between the used cooking oil and triglyceride profile with hypertension. Methods: The design of this study was observational analytic with cross-sectional research design. The sample of this study amounted to 96 people with purposive sampling technique. The instrument of this study was Questionnaire to determine the used cooking oil and automatic Spectrophotometer (TRX-7010) to measure triglyceride profiles. Data analysis was performed by chi-square test with significance value p < 0,05. Results: The results of this study showed that there was a correlation between the used cooking oil and hypertension (p = 0.002) and triglyceride profile with hypertension (p = 0.004). Conclusions: Hypertension had a correlation with the used cooking oil and increase in triglycerideprofile.